058 Fibroblast growth factor binding protein 1 gene (FGFBP1) and hypertension — from pathway analysis to renal glomerulus. (22nd September 2015) - Tomaszewski, M; Charchar, F; Barnes, T; Maric, C; Zukowska-Szczechowska, E; Samani, N J
Abstract : Essential hypertension is a complex, multifactorial disease with a strong genetic component. Fibroblast growth factor 1 gene (FGF1) is one of the most relevant candidates having been associated not only with familial susceptibility to hypertension but also with up-regulation within the glomerulus of the human hypertensive kidney/Circulation 2007;116:1915–24/. We have hypothesised that systematic analysis of genes interacting with FGF1 may uncover novel variants underlying essential hypertension. Seventy-nine common (minor allele frequency≥0.1) tagging (r2≥0.8) and functional single nucleotide polymorphisms (SNPs) spanning eight critical components of the FGF (fibroblast growth factor) pathway (FGF2, FGFR1, FGFR2, FGFR3, FGFR4, FGFBP1, FIBP, SPRY1) were genotyped by MALDI-TOF mass spectrometry in 629 subjects from 207 Polish hypertensive families (Silesian Hypertension Study — SHS). 83.5% of genotyped SNPs that passed quality control filters provided 92.9% genetic coverage of FGF pathway loci. Family-based analysis in SHS revealed that alleles of three SNPs (rs2956724, rs2245964 and rs16892645) in two loci (FGFR1 and FGFBP1) were transmitted to hypertensive offspring more frequently than expected by chance. However, only one association survived correction for multiple testing – major allele of rs16892645 in FGFBP1 was over-transmitted from heterozygous parents to hypertensive offspring more frequently than expected by chance(p=0.0048, false discovery rate<0.25). The association between rs16892645 and hypertension was replicated in an independent cohort of 807 Polish subjects from Silesian Cardiovascular Study — each major allele copy of rs16892645 increased the odds of hypertension approximately by 1.5 (odds ratio: 1.5; 95% CI: 1.1 to to 2.2, p=0.04). Association between FGFBP1 and hypertension was also apparent at the protein expression level — compared with normotensive patients, hypertensives from Silesian Renal Tissue Bank showed approximately 1.4-fold higher renal abundance of FGFBP1 in Western blotting (p=0.001). Immunohistochemical analysis revealed that hypertension-related up-regulation of FGFBP1 was exclusive to renal glomeruli. These data show that FGFBP1 — a gene that encodes a carrier protein for FGF1 — is associated with human hypertension. We also reveal that up-regulation of FGFBP1 maps to the same histological compartment where FGF1 was shown to be most abundant (renal glomeruli). Our study also proves that systematic genetic analysis of signalling pathways is a strategy with a potential to identify novel molecular mechanisms underlying blood pressure elevation.